Pengaruh Teknik Pembelajaran Listening Team Terhadap Hasil Belajar IPS Siswa - Khotimah, Husnul; Sumiyati, Sumiyati; Nurjannah, Nurjannah (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2017)
[Title:  Effect of Listening Team Learning Techniques on Student Social Studies Learning Outcomes].   The purpose of this study was to determine the effect of the listening team learning techniques on students’ social studies learning outcomes of SMK Negeri 2 Dompu in the 2016/2017 learning year. This research is a quasi-experimental study with a quantitative approach. The study sample consisted of 89 students consisting of two classes namely the experimental class (47 students) and the control class (42 students). The multiple choice form test instrument consisting of 20 test questions is used to obtain student learning outcomes data. The effect of listening team techniques on learning outcomes was tested using the t test. The results showed that the use of listening team techniques had no significant effect on students’ learning outcomes in social studies subjects of SMK Negeri 2 Dompu. The results of data analysis using the t-test formula show the value of tcount <ttable (0.007059 < 2.000). Based on the results, it can be stated that there is no significant effect of listening team techniques on students’ social studies learning outcomes of SMK Negeri 2 Dompu in the 2016/2017 learning year.